The interaction between reinforcement and inhibitory control in ADHD: A review and research guidelines. (March 2016) - Ma, Ili; van Duijvenvoorde, Anna; Scheres, Anouk
Abstract: The majority of studies which have aimed to identify cognitive and motivational factors at play in ADHD have investigated cognitive-control processes and reinforcement effects in isolation. Notably, in recent years, the interaction between these two processes has been increasingly examined. Here, we aimed to provide a comprehensive and critical review of the behavioral and functional neuroimaging studies that have investigated reinforcement effects on inhibitory control in ADHD. The findings of our meta-analyses show that reinforcement can normalize inhibitory control in children and adolescents with ADHD to the baseline level of controls. Furthermore, the data suggests that inhibitory control may improve to a larger extent in youth with ADHD compared with controls, as a function of reinforcement. Based on (1) this review and meta-analyses, (2) functional neuroimaging studies in healthy populations, and (3) existing ADHD and neurobiological models of dual processes, we propose specific guidelines for future research, which are anticipated to further elucidate processes underlying impulsive behavior associated with ADHD. Highlights: Qualitative and quantitative approaches were used to review reinforcement × inhibition interactions in children and adolescents with ADHD and controls. Meta-analyses show that reinforcement normalized inhibition in children and adolescents with ADHD to the baseline level of controls. Potential factors contributing to the reinforcement effects include the reinforcement schedules and the type of reinforcement. Future behavioral and neuroimaging research will help elucidate this interaction further.